Continuous Transitional Focus (CTF): A New Concept in Ophthalmic Surgery - Mesa, RR (2018)
Presbyopia is a condition that affects many as the lens ages, and is a secondary effect of cataract surgery. Multifocal lenses for the treatment of presbyopia have been undergoing cycles of development and improvement over the past two decades. The latest advancements have yielded lenses with a continuous range of optical powers, otherwise known as continuous transitional focus (CTF) lenses. Modern CTF lenses provide a more natural experience for patients while minimizing unwanted optical side effects.